Integrated evaporator–condenser cascaded adsorption system for low temperature cooling using different working pairs. (1st January 2017) - Dakkama, H.J.; Elsayed, A.; AL-Dadah, R.K.; Mahmoud, S.M.; Youssef, P.
Highlights: Five combinations of working pairs with cascading adsorption system are simulated. Integrated evaporator–condenser heat exchanger is simulated with the stated system. The low-temperature heat source is applied to drive the adsorption refrigeration system. Natural refrigerants are investigated as one of the requirements of this work. ATO/Ethanol + AC-35/Methanol showed a good performance with the lowest cost. Abstract: A cascaded adsorption cooling system with an integrated evaporator/condenser can produce low temperature cooling, using waste heat sources. The choice of the working pair in such a system affects the system's performance when driven by low temperature waste heat sources, which can be as low as 70 °C. This paper investigates the performance of various adsorbent/refrigerant working pairs in a cascaded adsorption system with an integrated evaporator/condenser using Simulink/MATLAB software. The cascaded system consists of two pairs of adsorber beds, a condenser, an evaporator and an integrated condenser/evaporator heat exchanger, forming upper and bottoming cycles. Five combinations of working pairs were investigated: ATO/ethanol + Maxsorb/R507A; Maxsorb/R134a + Maxsorb/propane; ATO/Ethanol + Maxsorb/propane; ATO/ethanol + AC-35/methanol; and Maxsorb/R134a + Maxsorb/R507A. The latter combination was used for validation and as a reference combination for assessing the performance of the investigated working pairs in terms of COP and cooling capacity. The results showed that the Maxsorb/R134a + Maxsorb/propane combination gives a higher COP compared to the reference combination, with up to 30.0% and 30.1% for the COP and cooling capacity, respectively; while ATO/ethanol + AC-35/methanol produces a similar performance to the reference case but uses natural refrigerants with low global warming potential and low cost adsorbent materials.